1998
DOI: 10.1192/pb.22.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Tattoos, scars, body adornment and dishevelment in an acute psychiatric population

Abstract: Ninety-six successive acute psychiatric admissions were assessed with regard to dress, level of hygiene, the presence of tattoos, bodily piercing/decoration and surface marks of self-harm. These features were also examined in relation to ICD-10 category diagnosis. One-third were described as 'dishevelled', 21% 'unclean', 7% had multiple pierced ears and 3% other pierced body parts. Sixteen per cent had tattoos, rising to 34% in the F10-19 (substance misuse) category, and 15% had scars of self-harm. People with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…One large uncontrolled survey (Ferguson-Rayport 1955) of first-time admissions to a psychiatric hospital found the overall prevalence rate of tattoos to be 16%, a finding subsequently replicated by Gittleson (1969), which found the prevalence rate to be 15%. A more recent study (Williams 1998) of psychiatric admissions found an overall prevalence rate of 16%. Psychiatric in-patients with tattoos appear to have a more chaotic and deprived upbringing than nontattooed controls.…”
Section: Prevalence In Psychiatric Populationsmentioning
confidence: 93%
See 4 more Smart Citations
“…One large uncontrolled survey (Ferguson-Rayport 1955) of first-time admissions to a psychiatric hospital found the overall prevalence rate of tattoos to be 16%, a finding subsequently replicated by Gittleson (1969), which found the prevalence rate to be 15%. A more recent study (Williams 1998) of psychiatric admissions found an overall prevalence rate of 16%. Psychiatric in-patients with tattoos appear to have a more chaotic and deprived upbringing than nontattooed controls.…”
Section: Prevalence In Psychiatric Populationsmentioning
confidence: 93%
“…Evidence of a relationship between tattoos and psychiatric disorders comes from studies of psychiatric pathology in tattooed individuals in non-psychiatric settings (Lander 1943;Measey 1972) and of tattooed psychiatric populations (Ferguson-Rayport 1955;Gittleson 1969;Raspa 1990;Inch 1993;Williams 1998). Both types of study report higher rates of alcoholism, drug misuse, impulsivity, risk-taking behaviour and personality disorders in both men and women (Lander 1943;Post 1968;Measey 1972;Buhrich 1982;Raspa 1990;Inch 1993).…”
Section: Tattoos and Psychiatrymentioning
confidence: 99%
See 3 more Smart Citations